PET/CT WITH 68GA-FAPI46 FOR THE DETECTION OF PRIMARY AND METASTATIC LESIONS IN PATIENTS WITH DIFFERENT TYPES OF CANCER. INITIAL EXPERIENCE - Lilian Yuri Itaya Yamaga; Gustavo Borges da Silva Teles; Durval Santos; Oren Smaletz; Roberto Pestana; Poliana Biasi; Mauricio Fernandes; Solange Amorim Nogueira; Marycel Figols Barboza; Taise Vitor; Jairo Wagner (Hematology, Transfusion and Cell Therapy)
Introduction/Justification: Fibroblast activation protein (FAP), a transmembrane glycoprotein, is over expressed by cancer-associated fibroblasts in the tumor microenvironment. Radiolabeled fibroblast activation protein inhibitors (FAPI) are currently being investigated for PET imaging. Objectives: To evaluate the diagnostic efficacy of PET/CT with fibroblast activation protein inhibitor (FAPI) labeled with gallium 68 (68Ga-FAPI46) for detecting primary and metastatic lesions in patients with different types of cancer. Materials and Methods: Patients with different types of cancer confirmed by histopathological study were evaluated with PET/CT with 68Ga-FAPI46 for initial staging or to detect tumor recurrence. The results of PET/CT were compared to the findings of conventional imaging methods such as computed tomography and magnetic resonance imaging and with FDG PET/CT and anatomopathological studies. Results: Thirty patients were evaluated, twenty two of whom were diagnosed with lung carcinoma, five with soft tissue sarcoma, one patient with each of the following tumors: gastric, breast and neuroendocrine carcinoma. High expression of FAPI was observed in most primary tumors. The diagnostic performance was high due to a favorable physiological organ distribution and low background signal leading to the detection of most metastatic lesions especially in lymph nodes, pleura, peritoneum, skeleton, liver and central nervous system. By contrast, there was false-positive 68Ga-FAPI46 uptake in inflammatory and infectious processes. Conclusion: PET/CT with 68Ga-FAPI46 is a promising imaging modality for the detection of primary and metastatic lesions of many types of cancer.